Morphological variation of the texanus white-tailed deer antlers in northeast Mexico - Cienfuegos-Rivas, E.G. (Universidad Autónoma de Tamaulipas, 2008)
The Mexican northeaster region is one of the most important ecological regions of the country, given its biodiversity. This biodiversity has favoured the hunting utilization of the wild species, one of this wildlife, the texano white-tailed deer (Odocoileus virginianus texanus) is considered to be the major hunting utilization animal. The objective of this study was to determine the morphometric variability of the texano white-tailed deer antler in the northeaster region of Mexico. There were obtained 1154 records of antlers of animals hunted and registered before the Asociación Nacional de Ganaderos Diversificados Criadores de Fauna (ANGADI) from 269 Animal Mangement Units (UMA) in 13 counties of the Nuevo León, Tamaulipas and Coahuila states. The ANGADI provided the antlers records that were based on the international Boone and Crocket system of measurement and modified by ANGADI. Initially and, to reduce the complexity of the system, there was realized an analysis of Principal Components. Due to the fact that the normality of the selected factors was not accepted (Kolmogorov- Smirnov’s Test with Lilliefors’s correction), the comparison of the distributions was realized by means of the no parametric test of Kruskall-Wallis or Mann-Whitney. The results indicated (two-tailed test) a marked effect of suplementación (Z = -4,678; P < 0,0001) and year (H4 = 43,301; P < 0,001) on total score and number of points of the antlers. Similarly, significant differences (H2 = 2.03; P < 0,0001) were found for the length of first point or defense among the eight points (4.01 ± 1,3 in, n = 202), typical (3,96 ± 1,3 in, n = 815) and atypical (4,63 ± 1,6 in, n = 85) deer. It was concluded that the environment has a significant effect on the morphometric variability of the antlers of the texanus white-tailed deer (O.v. texanus) in the northeast region of Mexico.